Villa-Lobos :música e nacionalismo na República Velha - Almeida, Washington Luiz Sieleman (2014)
This research purpose is to conduct an analysis of the initial career period of Heitor Villa-Lobos, during the Old Republic in Brazil (1889 - 1930). Also it will contextualise this process with cultural and economic policies and social changes from that period. Therefore there is a biographical study of him until 1930, pointing out the most important moments of his career in the period. It seeks to understand the factors that contributed to adopt a committed musical language with sound aspects of Brazil, and also, is displayed, with identification of Villa-Lobos as a nationalist composer. As so, we´re willing to question the importance and the musical quality of Villa-Lobos work, far beyond the myth of nationalism, trying to further understand how the cultural and social atmosphere of Rio de Janeiro, the capital of the newly founded Republic, influenced the works of Villa-Lobos.